2009
DOI: 10.1080/15504260902886505
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stressful Life Events on Alcohol Use Relapse: Findings From the Collaborative Longitudinal Personality Disorders Study

Abstract: Alcohol relapse is impacted by a variety of environmental, interpersonal, and intrapersonal factors. We examined the interaction between stressful life events, personality disorder subtype, and alcohol relapse among individuals enrolled in the Collaborative Longitudinal Personality Disorders Study (CLPS). Negative life events predicted relapse in all subjects. In individuals with a history of an alcohol use disorder prior to study entry, positive life events also predicted alcohol relapse. Individuals with Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(2 reference statements)
1
3
0
Order By: Relevance
“…Even though we did not objectively assess for stressful life events, we did observe that a majority of our participants with relapse had shared the details of both positive and negative life stress during their monthly follow-up visits. Christina et al, 23 observed, identical to our results, that unpleasant life experiences predicted relapse in all participants. Positive life experiences predicted alcohol relapse in persons who had a history of an alcohol use disorder before entering the study.…”
Section: Discussionsupporting
confidence: 91%
“…Even though we did not objectively assess for stressful life events, we did observe that a majority of our participants with relapse had shared the details of both positive and negative life stress during their monthly follow-up visits. Christina et al, 23 observed, identical to our results, that unpleasant life experiences predicted relapse in all participants. Positive life experiences predicted alcohol relapse in persons who had a history of an alcohol use disorder before entering the study.…”
Section: Discussionsupporting
confidence: 91%
“…The LEA was empirically established 20 and has been used in longitudinal studies of other psychiatric problems, including alcohol use disorders. 21 Participants are asked if any of a list of 82 events or circumstances occurred since the last follow-up interview. For any endorsed stressful events, participants are asked to provide the start and end dates for each specific event using the calendar for the interval period.…”
Section: Methodsmentioning
confidence: 99%
“…We focused on time-varying changes or fluctuations in these two forms of PD given 1 : this dimensional approach may have greater conceptual relevance and empirical validity 18,19 while providing greater statistical power 2 ; BPD and OCPD reflect contrasting behaviors (instability and impulsivity versus control and rigidity, respectively) associated with different patterns of ED, 14 functioning 19 and stressful life events 20 ; and cluster-B PD and OCPD have been found to be associated prospectively with higher versus lower rates, respectively, of alcohol use relapse. 21 We hypothesized that time-varying increases in negative life events would prospectively predict ED relapse and that, when considered jointly, time-varying increases in BPD criteria would increase ED relapse risk whereas increases in OCPD criteria would decrease ED relapse risk.…”
Section: Introductionmentioning
confidence: 99%
“…Women in poverty who experience severe, chronic life stressors are particularly vulnerable to psychological distress and problem drinking (Mulia, Schmidt, Bond, Jacobs, & Korcha, 2008). Life stressors have been shown to increase the risk of relapse in individuals with comorbid AUD and personality disorders (Reyes, Pagano, & Ronis, 2009). …”
Section: 0 Discussionmentioning
confidence: 99%